STRATEGI MARKETING PONDOK PESANTREN SALAF (Studi Kasus Pondok Pesantren Al-Bidayah Tegal Besar Kaliwates Jember) - Imam Wahyono; Ahmad Aziz Fanani (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
Marketing strategies in educational institutions, especially Islamic boarding schools, need to be done considering today's competition in educational institutions is very tight to get customers. To maintain the existence of the Salaf Islamic Boarding School and attract customer interest, perhaps the marketing strategy undertaken by the Al-Bidayah Islamic Boarding School Tegal Besar Kaliwates Jember can be imitated by other Salaf Islamic Boarding Schools. Because the Al-Bidayah Islamic Boarding School, apart from focusing on the study of the yellow book with the Al-Bidayah method, which is its trademark, the santri are allowed to continue in traditional schools outside the pesantren. This study aims to determine the marketing strategy of the salaf Islamic boarding school (a case study of the Al-Bidayah Islamic boarding school, Tegal Besar Kaliwates Jember. This research method uses qualitative research with the type of case study research. The data collection techniques are in-depth interview techniques, observation and documentation. The data analysis technique uses the theory of Miles & Huberman, while the validity of the data uses triangulation of sources. The results of this study indicate that the marketing strategy carried out by Islamic boarding schools adopts the theory of Kotler et al. known as The Seven PS (7P), namely: Product, Price, Place, Promotion, People, Physica Evidence, Process. Through this marketing strategy, the Al-Bidayah Islamic Boarding School can introduce a brand image characteristic of the pesantren, namely learning the yellow book with the Al-Bidayah method to the community. The increasing number of students yearly proves this, and many become champions in the MQK competition at the district, provincial and national levels.